2010
DOI: 10.1063/1.3487779
|View full text |Cite
|
Sign up to set email alerts
|

Analytical technique for subwavelength far field imaging

Abstract: We develop an analytical technique for retrieving the size and shape of subwavelength objects using far-field measurements. The approach relies on subwavelength diffraction gratings scattering evanescent information into the far field along with a numerical algorithm that is capable of deconvoluting this information based on the far-field intensity measurements. Several examples are presented, demonstrating resolution on the order of λ0/20. The developed method can be used at any frequency range, and may becom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…As a result, MEF often occurs with an increased excitation-relaxation cycling rate. In spite of these disadvantages, MEF and its related phenomena have found widespread use in fluorescence sensing [11-15], for novel probes [16-18], single molecule detection [19-21] and sub-diffraction limited microscopy [22-25]. …”
Section: Introductionmentioning
confidence: 99%
“…As a result, MEF often occurs with an increased excitation-relaxation cycling rate. In spite of these disadvantages, MEF and its related phenomena have found widespread use in fluorescence sensing [11-15], for novel probes [16-18], single molecule detection [19-21] and sub-diffraction limited microscopy [22-25]. …”
Section: Introductionmentioning
confidence: 99%
“…In recent papers [33,34], it was numerically demonstrated that using subwavelength gratings the surface waves from a point source could be converted into the propagating waves, thus achieving the superresolution of λ/20. This was implemented by means of several stacked diffraction gratings of different subwavelength periods and arbitrary apertures [33] and a metallic subwavelength grating with high permittivity (ε = -100) [34]. However, the use of focusing or imaging optical elements was not considered in the above works.…”
Section: Focal Spot Reduction By Modulation Of Refractive Indexmentioning
confidence: 99%
“…Numerical extraction of information about the unknown object was suggested as a basis for IMM in previous studies [14,15]. However, it was shown that in practice the implementation of such algorithms require extreme efforts in equipment calibration [15,24].…”
Section: Theoretical Analysismentioning
confidence: 99%
“…In interscale mixing microscopy (IMM) [14,15], a diffractive element is employed to out-couple information about sub-wavelength features of the object into the far field, similarly to SIM, with the final image formed using a post-processing of the information carried by multiple diffractive orders (Fig.1b). Although IMM somewhat resembles SIM and FSL, in contrast to the latter approaches, IMM utilizes multiple diffractive orders of the grating and therefore provides a resolution that is limited only by experimental noise.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation